Modernity, Sexuality, and Ideology in Iran: The Life and Legacy of a Popular Female Artist By Kamran Talattof (New York: Syracuse University Press, 2011. hbk. 288 pages.) (American Journal of Islam and Society, 2013)
Modernity, Sexuality, and Ideology in Iran represents a significant momentin artistic resurrection and re-vision. It examines the life and work of a discardedIranian female popular artist known as Shahrzad (b. 1946). Throughcritical attention previously denied to Shahrzad, Talattof honors her creativecontributions and, by extension, recognizes and honors artists like her whohave been marginalized for the last several decades, their art labeled as“shameful” or “profane” due to their unacceptable sexual roles as dancers,singers, and actresses. Through the lens of her life and legacy, he argues thattrue modernity can never fully emerge without space for the discussion ofsexuality – especially that of women.The author takes a risk in offering critical analysis of this artist’s life andwork, for Shahrazad is recognized neither in the canon, nor by the giants ofcommitted literature in Iran, the dominant style when she was writing in the1970s. While detailing and noting the significance of her accomplishments,he asks why she has not been so recognized and locates that question along aline of inquiry as regards Iran’s “missing” modernity. He asks why a nationwith such a long tradition of the scientific and socio-cultural accomplishmentsseems suddenly stuck in a medieval mindset, selectively applying modernityin such a way that it serves only to fortify the establishment in its extremepolicies – through such “modern” means as technology ...